2019
DOI: 10.1103/physrevx.9.021049
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dynamics of a Few-Photon Parametric Oscillator

Abstract: Modulating the frequency of a harmonic oscillator at nearly twice its natural frequency leads to amplification and self-oscillation. Above the oscillation threshold, the field settles into a coherent oscillating state with a well-defined phase of either 0 or π. We demonstrate a quantum parametric oscillator operating at microwave frequencies and drive it into oscillating states containing only a few photons. The small number of photons present in the system and the coherent nature of the nonlinearity prevents … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 38 publications
0
93
0
1
Order By: Relevance
“…Recently, a two-photon driven dissipative process based on superconducting circuits has been used to generate cat-like states in a microwave cavity [27,28]. Following the proposal by Mirrahimi et al [9], this demonstrates confinement of a state to a manifold mostly spanned by two coherent states with opposite phases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a two-photon driven dissipative process based on superconducting circuits has been used to generate cat-like states in a microwave cavity [27,28]. Following the proposal by Mirrahimi et al [9], this demonstrates confinement of a state to a manifold mostly spanned by two coherent states with opposite phases.…”
Section: Introductionmentioning
confidence: 99%
“…This is typically obtained in pyrochlore spin ices 112 and in honeycombs lattices 113 . Recent studies have further shown the possiblity of toggling the chirality of edge modes by tuning the DMI to exchange interaction ratio 114 or by inducing DMI by time-dependent interactions, or Floquet engineering 114,115 . The recently investigated kagome ice with nanoislands with varying anisotropies 57 could be a starting point to explore the onset of topological bands by pattering the structure on a heavy metal or by studying the next-nearest-neighbors interactions between the nanoislands.…”
Section: E Modellingmentioning
confidence: 99%
“…F2 accounts for the π-periodic component of the relative phase distribution and its sign determines the position of the peaks; F4 is the next largest, though it is much less important than F2, except for the region in which F2 passes through zero. The corresponding π 2 -periodic P (φ) distribution for the case where F2 is zero is shown in the inset; the peak-to-peak height is 10 −4 in units of (J/κ2) 4 .…”
Section: Synchronization Of Coupled Oscillatorsmentioning
confidence: 99%